Multicriteria FMECA Based Decision-Making for Aluminium Wire Process Rolling Mill through COPRAS-G. (14th July 2016) - Pancholi, Nilesh; Bhatt, M. G.
Abstract : This paper presents a multifactor decision-making approach based on "grey-complex proportional assessment (COPRAS-G) method" in a view to overcome the limitations of Failure Mode Effect and Criticality Analysis (FMECA). In this model, the scores against each failure mode are expressed in grey number instead of crisp values to evaluate the criticalities of the failure modes without uncertainty. The suggested study is carried out to identify the weights of major failure causes for bearings, gears, and shafts of aluminium wire rolling mill plant. The primary findings of the paper are that sudden impact on the rolls seems to be most critical failure cause and loss of power seems to be least critical failure cause. It is suggested to modify the current control practices with proper maintenance strategy based on achieved maintainability criticality index (MCI) for different failure causes. The outcome of study will be helpful in deriving optimized maintenance plan to maximize the performance of process industry.